Fungigação no controle do mofo branco e produtividade do feijoeiro em condições de cerrado brasileiro - Venegas, Fábio; Saad, João Carlos Cury [UNESP] (My University, 2010)
The aim of this research was to evaluate the white mold severity (Sclerotinia sclerotiorum (Lib.) of Bary), bean production components and yield (Phaseolus vulgaris L.), variety Perola, according to the application of procimidone fungicide (Sialex 500), through fungigation (center pivot) and automotive sprayer (Uniport). The study was carried under field production commercial conditions, in Primavera do Leste - MT - Brazil. The experiment consisted of 5 treatments (with 4 repetitions of 4 ha each), all with two procimidone applications (1.2 kg ha-1 each application, same as, 0.6 kg a.i. per hectare) to the 42 and 52 days after seeding. The water depths of 5.5 and 11.0 mm were tested in the application through central pivot (this had your checked uniformity), providing volumes of 55.000 and 110.000 L ha-1, respectively, and the volumes of 120 and 200 L ha-1 in the automotive sprayer. The severity of disease was evaluated by the percentage of the area affected by plant damage using diagramatic grade scale of white mold severity, as described by Azevedo (1998). The values were used to calculate the area under the disease progress curve (AUDPC). They were also analyzed, the number of the fungus apothecia during the crop cycle and the residual sclerotias weight in harvest. On this occasion, it was also evaluated the crop yield parameters: number of plants per plot (final stand), pods per plant, grains per pod, medium weight of 200 grains and productivity of grains. The AUDPC values, apothecia to 42, 49 and 56 days after seeding, sclerotias in 2 soil kg and the crop productivity parameters were submitted to the variance analysis and Tukey Test at 0.05 of probability. This test was also applied in the comparison among the different fungicide application methods, independent of spray volumes in each one. The statistical processing was accomplished by STAT program. The results showed that weren't differences among application techniques studied in relation to productivity parameters, however, best white mold control, smaller apothecia number to 49 and 56 days after seeding and smaller weight of residual sclerotias in the harvest were obtained with the fungigation, independently of the spray volume used.

O presente estudo objetivou determinar a severidade da doença mofo branco (Sclerotinia sclerotiorum (Lib.) de Bary) e os componentes de produção do feijoeiro (Phaseolus vulgaris L.), var. Pérola, submetido a aplicação do fungicida procimidone (Sialex 500), via fungigação (pivô central) e pulverizador automotriz (Uniport). O estudo foi realizado sob condições de produção comercial em campo, no município de Primavera do Leste - MT. O experimento constou de 5 tratamentos (com 4 repetições de 4 ha cada), sendo 4 deles envolvendo duas aplicações de procimidone (1,2 kg ha -1 cada aplicação), aos 42 dias e aos 52 dias após o plantio (DAP), e um deles sem aplicação deste produto, com delineamento experimental de blocos casualizados. Foram testadas as lâminas de água de 5,5 e 11,0 mm na aplicação via pivô central, proporcionando assim volume de calda de 55.000 e 110.000 L ha -1, respectivamente, e os volumes de 120 e 200 L ha -1 de calda no pulverizador automotriz. O critério adotado em todas as avaliações da severidade da doença foi o da porcentagem da área foliar lesionada utilizando escala diagramática de severidade da doença mofo branco. Os valores foram usados para calcular a área abaixo da curva de progresso de doença (AACPD). Foram analisados também, o número dos apotécios do fungo durante o ciclo da cultura e o peso dos escleródios residuais do patógeno na colheita. Nesta ocasião foram avaliados os seguintes componentes da produção da cultura: número de plantas por parcela (stand final), número de vagens por planta, número de grãos por vagem, peso médio de 200 grãos e produtividade de grãos. Os valores da AACPD, apotécios aos 42, 49 e 56 DAP, escleródios em 2 kg de solo e os parâmetros de produtividade da cultura foram submetidos à análise de variância e ao teste de comparação de médias de Tukey no nível de 5 % de significância, utilizando o programa computacional STAT. Nas condições experimentais em que se desenvolveu o trabalho, não foram constatadas diferenças significativas entre as diferentes técnicas de aplicação estudadas em relação ao parâmetros de produtividade, porém, melhores resultados de controle da doença mofo branco, menor número de apotécios por m2 aos 49 e 56 DAP e menor peso dos escleródios residuais na colheita foram obtidos com a aplicação do fungicida via pivô central, independentemente do volume de calda utilizado.
White mold control using fungigation and yield bean in Brazilian savannah conditions
Keywords: Fungigation; Phaseolus vulgaris l.; Sclerotinia sclerotiorum (Lib.) de bary; crop production; crop yield; disease control; fungicide; fungus; legume; pesticide application; savanna; Brazil; Mato Grosso; Primavera do Leste; Fungi; Phaseolus vulgaris; Sclerotinia sclerotiorum